Efficient and expressive bytecode-level instrumentation for Java programs - Soueidi, Chukri; Monnier, Marius; Falcone, Yliès (International journal on software tools for technology transfer, 2023)
We present an efficient and expressive tool for the instrumentation of Java programs at the bytecode level. BISM (Bytecode-Level Instrumentation for Software Monitoring) is a lightweight Java bytecode instrumentation tool that features an expressive high-level control-flow-aware instrumentation language. The instrumentation language is inspired by the aspect-oriented programming paradigm in modularizing instrumentation into separate transformers that encapsulate joinpoint selection and advice inlining, that is, the selection of points of interest in the execution and the execution of additional code at these points, respectively. BISM allows capturing joinpoints ranging from bytecode instructions to methods execution and provides comprehensive static and dynamic context information. It runs in two instrumentation modes: build-time and load-time. BISM also provides a mechanism to compose transformers and automatically detect when they interfere on the base program. Transformers in a composition can control the visibility of their advice and other instructions from the base program. We show several example applications for BISM and demonstrate its effectiveness using three experiments: a security scenario, a financial transaction system, and a general runtime verification case. The results show that (i) BISM instrumentation incurs low runtime and memory overheads, and (ii) the code produced by BISM performs better than the one produced by existing Java instrumentation tools.